2018
DOI: 10.1520/mpc20170130
|View full text |Cite
|
Sign up to set email alerts
|

Cold Compression of 7075 and Factors Influencing Stress Relief

Abstract: The residual stresses in heat treated 7075 aluminium alloy blocks have been characterised using neutron diffraction, x-ray diffraction and incremental centre hole drilling. Samples were quenched to induce high magnitude residual stresses which were then stress relieved by the controlled application of plastic deformation using a cold compression technique. The experimental variables investigated were the quench water temperature, and the post quench delay. This delay is considered to influence the final residu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…One aim of both experiments was to try to ensure each cold compressed block received the same amount of cold compression, and that the magnitude of the plastic strains applied would be small, so that measurable residual stress would remain within the blocks. Previous experiments on 7075 samples with the same geometry indicated that once the plastic strains exceeded 1%, the residual stresses were almost completely relieved [36,37].…”
Section: Resultsmentioning
confidence: 99%
“…One aim of both experiments was to try to ensure each cold compressed block received the same amount of cold compression, and that the magnitude of the plastic strains applied would be small, so that measurable residual stress would remain within the blocks. Previous experiments on 7075 samples with the same geometry indicated that once the plastic strains exceeded 1%, the residual stresses were almost completely relieved [36,37].…”
Section: Resultsmentioning
confidence: 99%
“…Other manufacturing steps may take place after quenching and prior to the machining step, including stress relief and ageing. For simple geometries such as rolled plates and sheets, stress relief by stretching is usually carried out, whereas cold compression is preferred for forged parts [34,41]. However, stress relief is often not possible for complex geometries [42].…”
Section: Remark 2 (On Stress Relief and Ageing)mentioning
confidence: 99%
“…Other manufacturing steps may take place after quenching and prior to the machining step, including stress relief and ageing. For simple geometries such as rolled plates and sheets, stress relief by stretching is usually carried out, whereas cold compression is preferred for forged parts [88,91]. However, stress relief is often not possible for complex geometries [90].…”
Section: Residual Stresses After Machiningmentioning
confidence: 99%